The Relationship Between Severity of Attention Deficit Hyperactivity Disorder (ADHD) with Maternal Anxiety - Yunias Setiawati; H. J. Mukono; Joni Wahyuhadi; Endang Warsiki (Health Notions, 2018)
Attention deficit hyperactivity disorder (ADHD) is the most common childhood neurobiologic disorder with main symptom of inattention, hyperactivity, impulsivity and minimal occurrence in two different place settings, for example at home and at school. ADHD disorders will last sustainably from adolescence to adulthood. Mothers of ADHD children tend to be anxious, tired and desperate because they are often blamed by the environment for failing to educate children due to opposing children's behavior, disobeying orders that result in ADHD children being rejected and experiencing low learning achievement. Mothers are also often must lose his job due to having to take care of his own ADHD child.Methods: Observational analytic study with cross sectional design of 30 mothers of ADHD children aged 6 to 12 years of Bina Karya primary school Surabaya by random sampling method. Assessment of ADHD by mothers using SPAHI (Skala Penilaiana Anak Hiperaktif Indonesia) and maternal anxiety assessment using Hamilton Anxiety Rating Scale questionnaire Results: there was significant correlation between maternal anxiety level and severity of ADHD with score p = 0.003 and r = 0.530 Conclusion: The degree of maternal anxiety is related to the severity of ADHD. Keywords: ADHD, Maternal anxiety